The Electrostatic Model of Homeopathy: The Mechanism of Physicochemical Activities of Homeopathic Medicines - Shahabi, Shahram; Borneman, John P. (Homeopathy, 2021)
This paper attempts to propose a model, called the electrostatic model of homeopathy, to explain a mechanism for the physicochemical activities of highly diluted homeopathic medicines (HMs). According to this proposed model, the source of HMs' action is dipole orientations as electrostatic imprints of the original molecules carried by diluent molecules (such as sugar molecules) or potentization-induced aqueous nanostructures. The nanoscale domains' contact charging and dielectric hysteresis play critical roles in the aqueous nanostructures' or sugar molecules' acquisition of the original molecules' dipole orientations. The mechanical stress induced by dynamization (vigorous agitation or trituration) is a crucial factor that facilitates these phenomena. After dynamization is completed, the transferred charges revert to their previous positions but, due to dielectric hysteresis, they leave a remnant polarization on the aqueous nanostructures or sugar molecules' nanoscale domains. This causes some nanoscale domains of the aqueous nanostructures or sugar molecules to obtain the original substance molecules' dipole orientations. A highly diluted HM may have no molecule of the original substance, but the aqueous nanostructures or sugar molecules may contain the original substance's dipole orientations. Therefore, HMs can precisely aim at the biological targets of the original substance molecules and electrostatically interact with them as mild stimuli.
Keywords: homeopathy; mechanism; electrostatic; aqueous nanostructures